Pathogenicity and Genomic Analysis of Hypervirulent Aeromonas hydrophila NN0116 From Nile Tilapia and Head Kidney Transcriptome of Infected Fish Reveals a B‐Cell‐Dominated Immune Response - Fuhao Geng; Jifeng Zhang; Zulin Fang; Zhengshuang Li; Guixiang Tong; Qi Li; Youchuan Wei (Journal of Fish Diseases, 2026)
Aeromonas hydrophila is a major pathogen of Motile Aeromonad Septicemia (MAS) in Nile tilapia, with pathogenesis and immunity poorly understood. In early 2026, a > 70% mortality outbreak occurred at a Nanning tilapia farm. The dominant strain NN0116 was identified as A. hydrophila by 16S rRNA and whole‐genome ANI analysis. It exhibited high virulence (LD 50 = 5.2 × 10 3 CFU/fish). Its 5.37 Mb genome encodes 5065 proteins and contains T2SS, T3SS, T6SS, and pore‐forming toxins. Virulence and antimicrobial resistance genes co‐localized on genomic islands GI2 and GI7. The strain was resistant to 12 antibiotic classes but susceptible to third‐generation cephalosporins and fluoroquinolones. Head kidney transcriptomics at 24 h identified 1066 differentially expressed genes, including 61 immunoglobulin (Ig) genes. KEGG enrichment revealed 43 significant pathways; the top ten were driven by 26 Ig genes. Network analysis of the top 20 pathways identified B cell receptor signalling (ko04662) and COVID‐19 (ko05171) as central nodes, alongside 10 secondary core pathways, all Ig‐driven. Integration of bacterial genomic and host transcriptomic data characterizes hypervirulent A. hydrophila NN0116 and demonstrates that Ig‐mediated B cell responses are central to host defence, offering targets for vaccines and therapeutics.